Impact of severe drought on biogenic volatile organic compounds emissions from Sphagnum mosses in boreal peatlands - Männistö, Elisa; Ylänne, Henni; Kokkonen, Nicola; Korrensalo, Aino; Laine, Anna M.; Yli-Pirilä, Pasi; Keinänen, Markku; Tuittila, Eeva-Stiina (Elsevier, 2024)
Climate change and the associated increased frequency of extreme weather events are likely to alter the emissions of biogenic volatile organic compounds (BVOCs) from boreal peatlands. Hydrologically sensitive Sphagnum mosses are keystone species in boreal peatland ecosystems that are known to emit various BVOCs. However, it is not known how their emissions respond to seasonal droughts. In this study, we quantified the effect of severe drought, and subsequent recovery, on the BVOC emissions from Sphagnum mosses using mesocosms originating from wet open and naturally drier treed boreal fens and bogs. Here we report the emissions of 30 detected BVOCs, of which isoprene was the most abundant with an average flux rate of 5.6 μg m−2 h−1 (range 0–31.9 μg m−2 h−1). The experimental 43-day ecohydrological drought reduced total BVOC and isoprene emissions. In addition, in mesocosms originating from bogs, sesquiterpene emissions decreased with the drought, while the emissions of green leaf volatiles were induced. Sesquiterpene emissions remained low even six weeks after rewetting, indicating a long and limited recovery from the drought. Our results further imply that long-term exposure to deep water tables does not decrease sensitivity of Sphagnum to an extreme drought; we did not detect differences in the emission rates or drought responses between Sphagna originating from wet open and naturally drier treed habitats. Yet, the differences between fen and bog originating Sphagna indicate local variability in the BVOC quality changes following drought, potentially altering the climate feedback of boreal peatland BVOC emissions.
Keywords: isoprene; mires; sesquiterpenes; water table; bogs; fens